APAKAH KUALITAS PRODUK, PERSEPSI HARGA, DAN KUALITAS PELAYANAN BERPENGARUH TERHADAP KEPUASAN KONSUMEN PADA WARUNG MIE AYAM PAK PUR KENDAL? - Finejuni, Cesar; Yudha, Muhammad Kurnia; Octavia, Ayu Nurafni (Fakultas Ekonomi, Bisnis dan Humaniora, 2025)
This research aims to analyze how much influence the independent variables, namely product quality, price perception and service quality, have on the dependent variable of consumer satisfaction at Mr Pur Kendal Chicken Noodle Shop. This research uses quantitative methods. The data in this research was collected through a survey method using purposive sampling techniques. Questionnaires were distributed to 96 respondents who had made a purchase at Mr Pur Kendal Chicken Noodle Shop at least once. The data resulting from distributing the questionnaire will be processed using the SPSS software analysis tool. The selected test results and analysis include validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis testing via t test, F test, and analysis of the coefficient of determination (R2). From the research results and data analysis results, the following conclusions can be drawn: there is a positive and significant influence of product quality variables on consumer satisfaction at Mr Pur Kendal Chicken Noodle Shop. There is a positive and significant influence of the price perception variable on consumer satisfaction at Mr Pur Kendal Chicken Noodle Shop. There is a positive and significant influence of service quality variables on consumer satisfaction at Warung Mie Ayam Pak Pur Kendal. Simultaneous test results show that the variables of product quality, price perception and service quality have a significant effect on consumer satisfaction at Mr Pur Kendal Chicken Noodle Shop.